Solid-calcified colloid cyst of the third ventricle - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
We report a 65-year-old female with a solid-calcified colloid cyst in the third ventricle that was demonstrated on computed tomography scan and magnetic resonance images. The lesion was surgically excised using the anterior transcallosal-transforaminal approach. Complete preservation of the surrounding neural and vascular structures was achieved. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: colloid cyst; third ventricle; transcallosal-transforaminal approach; 3RD VENTRICLE; EXPERIENCE; MANAGEMENT; RESECTION